Reframing Violence: A Philosophical Comparison of Physical and Non-Physical Sexual Violence in Indonesian Criminal Law - Lidinillah, Endin (Jurnal Syariah dan Hukum Komparatif, 2025)
Indonesian Law Number 12 of 2022 on the Sexual Violence Crimes (TPKS) identifies sexual harassment—both non-physical and physical—as a form of sexual violence punishable by imprisonment and/or fines. However, there is a significant distinction in its legal classification. Non-physical sexual harassment is treated as a complaint-based offense (delik aduan), meaning it can only be prosecuted if reported by the victim. In contrast, physical sexual harassment may be categorized as either a complaint-based offense or a public offense (delik biasa), the latter allowing law enforcement to initiate proceedings without a formal complaint. This paper critically examines the alignment between these legal classifications and the philosophical foundations set forth in the preamble of the TPKS Law and its Academic Paper. Utilizing a normative juridical approach, the study draws from primary legal sources and the academic paper, analyzed through qualitative descriptive methods, including data reduction, presentation, and conclusion drawing. The study finds that the differentiation between complaint-based and public offenses for sexual harassment is inconsistent with the law’s stated philosophical values, which emphasize the protection of human dignity and the prevention of sexual violence as a matter of public interest.